Use of the Critical Acidification Model to Estimate Critical Localized Corrosion Potentials of Duplex Stainless Steels - Iannuzzi, Mariano; Kappes, M.; Rincon Ortiz, M.; Carranza, R. (NACE International, 2016)
Crevice corrosion affects the integrity of stainless steels used in components exposed to seawater. Traditionally, crevice corrosion testing involves the use of artificial crevice formers to obtain a critical crevice potential, which is a measure of the crevice corrosion resistance of the alloy. The critical acidification model proposed by Galvele predicts that the critical crevice potential is the minimum potential required to maintain an acidic solution with a critical pH inside either a pit or a crevice. Application of Galvele’s model requires an estimation of both the diffusion length and the i vs. E behavior of the metal in the solution inside the crevice. In this work, the crevice corrosion resistance of a 22%Cr duplex stainless steel (UNS S31803) and a 25%Cr super duplex stainless steels (UNS S32750) was investigated. The i vs. E response of the two stainless steels was determined in acidified solutions of various chloride concentrations, which simulate those found in an active crevice. Critical potentials predicted by the critical acidification model were compared with critical crevice potentials measured in simulated seawater. Results showed that despite the various assumptions and simplifications made by Galvele, the model correctly predicted the occurrence of crevice corrosion of both 25Cr super duplex stainless steel and 22Cr duplex stainless steel close to room temperature in a 3.5 wt% NaCl environment. Critical potentials obtained by Galvele’s model were similar if assuming that the chloride concentration of the simulated crevice solutions was between 7 M and 12 M acidified to a pH of 0.